Association between glycemia risk index and carotid intima-media thickness in type 2 diabetes - Zhao, Lingyun; Heng, Hongyan; Xie, Qinyuan; Liang, Chenghong; Guo, Sijia; Zhang, Ziyi; Yuan, Huijuan (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the association between the Glycemic Risk Index (GRI) and carotid intima-media thickness (CIMT) in type 2 diabetes mellitus (T2DM) patients and evaluate the clinical utility of GRI for early vascular risk assessment.MethodsThis retrospective study included 450 previously untreated patients with T2DM prior to hospitalization. We calculated GRI using CGM data and assessed CIMT with high-resolution ultrasound. Multiple linear and logistic regression analyses assessed the association between GRI and CIMT. Receiver operating characteristic (ROC) curve analyses evaluated GRI’s predictive performance.ResultsThere was a significant positive correlation between GRI and CIMT (r = 0.42, P < 0.001). After adjusting for confounders, GRI remained an independent predictor of CIMT thickening (OR = 7.226, 95% CI: 5.597–8.856, P < 0.001). ROC analysis revealed that GRI alone predicted abnormal CIMT with an AUC of 0.869.ConclusionGRI is a robust marker for predicting CIMT thickening in T2DM patients, providing a novel approach for cardiovascular risk stratification. This study underscores the potential of integrating GRI into routine diabetes management to improve vascular outcomes.